Kajian Perubahan Ruang Terbuka pada Kawasan Bersejarah dengan Metode Space Syntax (Studi kasus Kawasan Kampung Kapitan Palembang (The Study of Open Space Change in Heritage Area Using Space Syntax Method (The Case of Kapitang Kampung, Palembang)) - Johannes Adiyanto (The Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
The understanding of void in solid-void theory cannot be ignored since urban open space is, in fact, the connector between existing buildings. Here also social interaction takes place between people living around that urban open space. In historic areas urban open space is very important, not only as a place to socialize but also due to its ecological and spiritual meaning. The area of Kampung Kapitan is one of the historic areas in Palembang. However, developments in this area have ignored the aspect of conservation . By using space syntax analysis which can analyze changes in spatial configuration in a qualitative way, this paper proves that conservation of a heritage area not just focuses on its buildings, but also on the surrounding area, whih includes open space. This is signified so the sustainability of historic areas can be guarded in accordance with Law no. 11/2010.